ODSC East 2019 (Open Data Science Conference - Conference, ODSC (Addison-Wesley Professional, 2020)
ODSC East 2019 Royalties for this video set help fund the ODSC Grant Award for open source data science projects. The Open Data Science Conference has established itself as the leading conference in the field of applied data science. Each ODSC event offers a unique opportunity to learn directly from the core contributors, experts, academics and renowned instructors helping shape the field of data science and artificial intelligence Presentations cover not only data science modeling but also the languages and tools needed to deploy these models in the real world such as TensorFlow, MXNet, scikit-learn, Kubernetes, and many more. Our conferences are organized around focus areas to ensure our attendees are at the forefront of this fast emerging field and current with the latest data science languages, tools, and models. You'll find in our East 2019 video catalog some of our most popular focus areas. Please see our table of contents for a full list of videos